(untitled) (Revista Contexto & Educação, 2021)
The article presents understandings of an ethno-research-formation with teachers, about dialogical research in the science classroom. It covers the constitution of the empirical field, delimiting the analysis of 43 reports produced by professors of the field of Natural Sciences (Chemistry, Physics, Biology and Sciences) under formation in the 2016 and 2017 editions of the CIRANDAR extension project: research circles since the school, developed at a Brazilian Public University in partnership with Basic Education Schools. The analysis is based on the language expressed in the textual productions, in which empirical information emerged from the research, based on the guiding question of the study. What is this from research in the reports of science teachers in CIRANDAR? It is assumed that ethno-research-formation in a hermeneutic phenomenological approach as a means of epistemological construction. The information was analyzed following the principles of Discursive Textual Analysis (ATD), in which four final categories emerged. In this text, we present understandings related to category IV) Dialogical inquiry in the science classroom, which shows the dialogical investigation is assumed by the analyzed teachers’ collective, as a didactic-pedagogical strategy triggered by the problematization, with questions from students and teachers when operating, collectively, information. and scientific language in constituting, negotiating and communicating meanings in the science classroom.